2013
DOI: 10.5958/j.2319-5886.2.3.085
|View full text |Cite
|
Sign up to set email alerts
|

Validation of endometrial curettage in abnormal uterine bleeding in a teaching institute of central India: A prospective study

Abstract: Abnormal uterine bleeding (AUB) is one of the common reasons for female patients to consult a gynecologist. AUB include bleeding from structural causes like polyps, endometrial hyperplasia, chronic endometritis, proliferative endometrium, fibroids, carcinoma and pregnancy related complication and dysfunctional uterine bleeding. Methods: A prospective study done in one year duration among 210 patients of 20-70 years age group. A tissue sample is taken after endometrial curettage and examined by a pathologist f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…Atrophic endometrium was seen predominantly in postmenopausal age group, the reason is that decreased estrogenic stimulation leads to thin atrophic endometrium making it susceptible to minor injury and may cause bleeding even in absence of any identifiable lesion. 23 Hyperplasia was (n=26, 8.67%) and comparable to other authors 9.1%, 18 10.92% 7 ; 6.11% 24 and 12.6% 8 but it is much lower than 41.9%, 10 30.3%, 4 25% 22 and 25.5%. 21 In this study 61.5% of hyperplasia was noted in perimenopausal age group.…”
Section: Paritysupporting
confidence: 87%
See 1 more Smart Citation
“…Atrophic endometrium was seen predominantly in postmenopausal age group, the reason is that decreased estrogenic stimulation leads to thin atrophic endometrium making it susceptible to minor injury and may cause bleeding even in absence of any identifiable lesion. 23 Hyperplasia was (n=26, 8.67%) and comparable to other authors 9.1%, 18 10.92% 7 ; 6.11% 24 and 12.6% 8 but it is much lower than 41.9%, 10 30.3%, 4 25% 22 and 25.5%. 21 In this study 61.5% of hyperplasia was noted in perimenopausal age group.…”
Section: Paritysupporting
confidence: 87%
“…Sadia khan 8 Parity: In the present study, the highest incidence of AUB was seen in multiparous women this is in similarity with other authors as shown in table 4 as well as by most other investigators. 10,12 The lowest incidence of AUB was seen in nulliparous women in the present study (3%) which is in close similarity with Radha N 12 (4%) and Sadia K 8 (5.4%).…”
Section: Paritysupporting
confidence: 85%
“…Endometrial hyperplasia (25%) is the leading pathological finding in this study and is of cystic type, this figure was similar to the study done by Damle et al 4 , Arti Anvikar et al 8 and A Khare 11 . A higher incidence of 41.9% was reported by Smita et al 6 . Identification of endometrial hyperplasia is important because they are thought to be precursors of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 68%
“…It was the most common clinical presentation seen in other studies also. [4][5][6][7][8] DUB has great variation in the endometrial patterns and its management entirely depends upon the type of endometrial pattern. Our study like several others showed that proliferative, 11 and A Khare et al 12 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion criteria, the 152 women's medical data, clinical information and endometrial histopathology finding were evaluated. 152 women patients who were diagnosed with abnormal uterine bleeding, their ages ranged from 23 Figure 2 The 152 cases were distributed depending on marital status and majority about 91.45 % were married and 8.55% were unmarried.…”
Section: Resultsmentioning
confidence: 99%